168k views
2 votes
If you can solve it.Thanks in advance

If you can solve it.Thanks in advance-example-1
User Loz
by
4.9k points

1 Answer

1 vote

Answer:


f(g(x))=(1)/((x^(2)+1)^(2)) +\sqrt[3]{x^(2)+1}

Explanation:

we have


f(x)=x^(2) +\frac{1}{\sqrt[3]{x}}


g(x)=(1)/(x^(2)+1)

we know that

In the function


f(g(x))

The variable of the function f is now the function g(x)

substitute


f(g(x))=((1)/(x^(2)+1))^(2) +\frac{1}{\sqrt[3]{((1)/(x^(2)+1))}}


f(g(x))=(1)/((x^(2)+1)^(2)) +\sqrt[3]{x^(2)+1}

User RohinNZ
by
5.2k points